2015
DOI: 10.1039/c4md00399c
|View full text |Cite
|
Sign up to set email alerts
|

4-Thiazolidinone derivatives as potent antimicrobial agents: microwave-assisted synthesis, biological evaluation and docking studies

Abstract: As a part of our ongoing research in the development of new antimicrobials, herein, we report the synthesis of ten compounds which combine three bioactive moieties: thiazole, adamantane and 4-thiazolidinone. Evaluation of their antibacterial activity revealed that the newly synthesized compounds exhibited remarkable growth inhibition of a wide spectrum of Gram-positive bacteria, Gram-negative bacteria and fungi. The majority of the compounds displayed greater antibacterial activity than the reference drugs (am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 54 publications
4
23
0
Order By: Relevance
“…Again, the formation of the hydrogen bond between the C=O group and Ser228 was observed. Thus, the obtained results support previous data [ 69 , 70 , 71 , 72 ] that MurB maybe is the most appropriate target for the antibacterial activity for this chemical series.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Again, the formation of the hydrogen bond between the C=O group and Ser228 was observed. Thus, the obtained results support previous data [ 69 , 70 , 71 , 72 ] that MurB maybe is the most appropriate target for the antibacterial activity for this chemical series.…”
Section: Resultssupporting
confidence: 89%
“…It was found that benzothiazole derivatives are mentioned as Gyrase inhibitors [ 66 , 67 , 68 ]. On the other hand, according to the literature, thiazolidinones act as MurB inhibitors [ 69 , 70 , 71 , 72 ]. Furthermore, prediction of the mechanism of action by computer program PASS indicated Thymidylate kinase as the probable antibacterial target.…”
Section: Resultsmentioning
confidence: 99%
“…Inspection of the binding mode and pocket revealed that compounds 5 b‐d exhibit three hydrogen bonds in addition to the cation‐π interactions with the protein active site residue Arg 188. As previously reported regarding MurB protien residues in the active site,, all the docked compounds that exhibited antibacterial activity interacted with Arg 188, Ser 238, Gln 229 which are strictly conserved in the S. aureus active site. The important interactions of the 2,4‐dichloro compound 5 b includes two hydrogen bonds between the N of N=C and Arg 188 and another bond between Gln 229 and the N of the isoxazole with distances of 1.93 and 1.97 Å, respectively.…”
Section: Resultssupporting
confidence: 76%
“…Molecular docking is a technique of simulation of molecular systems, which aids in the virtual screening and rational design of compounds to predict their bioactivities before being synthesized. Based on the reports which exhort the inhibition of MurB protein by 4-thiazolidinone derivatives [21,22], the title compound was docked into the active pocket of the enzyme. A literature survey and structure-activity relationship studies revealed the fact that the antibacterial property not only depended on the 4-thiazolidinone core, but also on the nature and positions of the substituents on the ring [23].…”
Section: Introductionmentioning
confidence: 99%